Multiple same day cryolipolysis treatments for the reduction of subcutaneous fat are safe and do not affect serum lipid levels or liver function tests - Klein, Kenneth B.; Bachelor, Eric P.; Becker, Edward V.; Bowes, Leyda E. (Lasers in surgery and medicine, 2017)
Objective Cryolipolysis is a safe and effective non‐surgical procedure for reducing subcutaneous fat. It spares adjacent structures, is associated with few adverse events, and is well‐tolerated by patients. Previous studies involving one or two simultaneous treatment sites have shown no effect on serum lipid levels or liver tests. The purpose of this study was to determine whether multiple same day treatments (abdomen plus both flanks) result in changes in these blood tests, and is safe. Study Design Thirty‐five adult males and females underwent same‐day cryolipolysis (CoolSculpting System, ZELTIQ Aesthetics) of the lower abdomen and flanks for reduction of subcutaneous fat. Serum lipids and liver tests were measured prior to treatment and at 1, 4, and 12 weeks post‐treatment. Expected treatment side‐effects were assessed immediately post‐treatment and at the 12‐week follow‐up visit. Adverse events were also monitored. Methods Treatment consisted of one cycle to the lower abdomen using a large vacuum applicator and simultaneous treatment of both flanks, one cycle each, with medium vacuum applicators .Time between the abdomen and flanks procedures was not to exceed 30 minutes. Results The procedures were well‐tolerated by patients; expected treatment effects were in general mild or moderate, and resolved without intervention. There were no clinically meaningful changes from baseline to any subsequent time point in any serum lipid test. This was also true for all liver tests. There were no treatment‐related adverse events. Conclusion Multiple cycle, same day cryolipolysis treatment of the lower abdomen and both flanks is well‐tolerated and safe. It does not lead to changes in serum lipids or liver tests at any of the measured time points following the procedure. Lasers Surg. Med. 49:640–644, 2017. © 2017 The Authors. Lasers in Surgery and Medicine Published by Wiley Periodicals Inc.